The transdiagnostic role of food craving: An application of substance use models. (1st March 2022) - Verzijl, Christina L.; Gius, Becky; Schlauch, Robert; Rancourt, Diana
Abstract: Food craving is a transdiagnostic process underlying clinically significant disordered eating behaviors and eating disorder diagnoses. However, the lack of literature examining the role of food craving as it relates to the full spectrum of disordered eating behaviors, including restrictive eating and compensatory behaviors, may be due to the traditional definition of food craving as the desire to consume particular foods. Applying motivational models of substance use craving to food craving may help to explain inconsistencies within existing literature. Three motivational models of craving from the substance use literature may be particularly applicable to (1) provide a clear definition of food craving as a motivational process, (2) understand the role of that motivational process as it underlies the full spectrum of disordered eating behavioral patterns, (3) provide insight for the most appropriate ways in which to accurately assess food craving, and (4) establish ways in which food craving may represent a useful motivational process to target in eating disorder treatments. This narrative review describes three models of substance use craving and provides suggestions for utilizing motivational models to understand the transdiagnostic role of food craving as it relates to the full spectrum of disordered eating behaviors in both research and clinical work.